A glacial survivor of the alpine Mediterranean region: phylogenetic and phylogeographic insights into Silene ciliata Pourr. (Caryophyllaceae) - Kyrkou,Ifigeneia; Iriondo,José María; García-Fernández,Alfredo (PeerJ, 2015)
Silene ciliata Pourr. (Caryophyllaceae) is a species with a highly disjunct distribution which inhabits the alpine mountains of the Mediterranean Basin. We investigated the phylogeny and phylogeography of the species to (a) clarify the long-suggested division of S. ciliata into two subspecies, (b) evaluate its phylogenetic origin and (c) assess whether the species’ diversification patterns were affected by the Mediterranean relief. For this purpose, we collected DNA from 25 populations of the species that inhabit the mountains of Portugal, Spain, France, Italy, former Yugoslav Republic of Macedonia, Bulgaria and Greece and studied the plastid regions rbcL, rps16 and trnL. Major intraspecific variation was supported by all analyses, while the possibility of the existence of more varieties or subspecies was not favoured. Plastid DNA (cpDNA) evidence was in accordance with the division of S. ciliata into the two subspecies, one spreading west (Iberian Peninsula and Central Massif) and the other east of the Alps region (Italian and Balkan Peninsula). This study proposes that the species’ geographically disconnected distribution has probably derived from vicariance processes and from the Alps acting as a barrier to the species’ dispersal. The monophyletic origin of the species is highly supported. cpDNA patterns were shown independent of the chromosome evolution in the populations and could have resulted from a combination of geographic factors providing links and barriers, climatic adversities and evolutionary processes that took place during Quaternary glaciations.
Keywords: Silene ciliata; Mediterranean Basin; cpDNA markers; Pleistocene glaciations; Phylogeography; Phylogeny; Alpine plant; Subspecies; Silene genus